Factors affecting treatment outcome among Pulmonary Tuberculosis patients under RNTCP in urban Pondicherry, India - M, Veerakumar A; Sahu, Swaroop Kumar; Sarkar, Sonali; Kattimani, Shivanand (Indian Journal of Community Health, 2016)
Background: Many factors associated with unsuccessful TB treatment outcome. Objective: To find out the factors affecting treatment outcome among Pulmonary Tuberculosis patients under RNTCP in urban Pondicherry, Methods: A cross-sectional study was conducted among 265 PTB patients from 6 randomly selected urban PHCs of Pondicherry from Jan 2013 to March 2014. A Pre-tested questionnaire was used. Data were entered in Epi-data v3.1 and was analysed by SPSS v20. Chi-square test and multiple logistic regressions were used. Results: Out of 265 patients registered 235 (88.7%) patients were included. The Majority were males (79.6%), and Mean (SD) age was 44±14 years. The Majority (83.4%) were formally educated, 74% were employed, and 77% received Cat I treatment. Prevalence of alcohol drinkers, current smokers and smokeless users was 31.5%, 23.5%, 9.4% respectively. A total of 14.5% had bad treatment Outcome Univariate analysis showed that Current smoker and Category II PTB treatment had significantly associated with bad outcome (p value-<0.05). In Multivariate analysis, Category II PTB treatment [AOR = 3.5 (1.6-7.8)] had significantly associated with bad outcome (p value-<0.05) after adjusted with age group, gender, Smoking and alcohol status Conclusion: Current Smoking and Category II PTB Treatment were the major factors affecting the TB treatment outcome